2022
DOI: 10.1177/09544062221077163
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Ripple Nanostructure Formation During Nanomachining via Atomic Force Microscopy

Abstract: Molecular dynamics (MD) constant force simulation mode is first used to study the formation of the ripple nanostructures on the single-crystal copper surface by combining the topography generated by machined grooves with the accumulated pile-up material on the side of these grooves via a triangular pyramid atomic force microscopy (AFM) tip. Groove morphologies, lateral forces, the evolution of subsurface defects, and atomic flow laws generated by different machining parameters are discussed. Specifically, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Guo et al used MD simulation to study the effect of process parameters on the cutting process of polycrystalline γ-TiAl alloy workpieces, and concluded that the average cutting force and friction coefficient increase with the increase of the depth of cut; increasing the cutting speed will induce amorphization of the material and plastic side flow, leading to a significant increase in the contour peaks on both sides of the machined surface [21]. Geng et al used MD simulation to study the effect of cutting force on atomic flow and material buildup [22]. Ren et al conducted MD simulation on the cutting process of single-crystal Cu workpiece, and found that the cutting force and cutting temperature are more sensitive to the change of the tool rake angle, and derived the critical clearance angle of the cutting tool, which has no effect on the machined surface after the clearance angle of the tool exceeds the critical value [23].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al used MD simulation to study the effect of process parameters on the cutting process of polycrystalline γ-TiAl alloy workpieces, and concluded that the average cutting force and friction coefficient increase with the increase of the depth of cut; increasing the cutting speed will induce amorphization of the material and plastic side flow, leading to a significant increase in the contour peaks on both sides of the machined surface [21]. Geng et al used MD simulation to study the effect of cutting force on atomic flow and material buildup [22]. Ren et al conducted MD simulation on the cutting process of single-crystal Cu workpiece, and found that the cutting force and cutting temperature are more sensitive to the change of the tool rake angle, and derived the critical clearance angle of the cutting tool, which has no effect on the machined surface after the clearance angle of the tool exceeds the critical value [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the nanoscratching method, the probe geometry, scratching direction and feed direction are the key factors for the machining outcomes. 21 For the nanoindentation method, Chang et al 17 and Yao et al 18 processed micro/nano-pits array on the Au films by Berkovich indenter, and they used the nano-pits array as a SERS substrate to detect the hepatitis virus antigen at low concentrations. Yan et al 19 and Jeon et al 20 utilized spherical indenter to machine indentations on metals used as molds, and the modes could be used to fabricate lens array.…”
Section: Introductionmentioning
confidence: 99%